Both CD4+ and CD8+ Lymphocytes Participate in the IFN-γ Response to Filamentous Hemagglutinin from Bordetella pertussis in Infants, Children, and Adults - Violette Dirix; Virginie Verscheure; Françoise Vermeulen; Iris De Schutter; Tessa Goetghebuer; Camille Locht; Françoise Mascart (Clinical and Developmental Immunology)
Infant CD4+ T-cell responses to bacterial infections or vaccines have been extensively studied, whereas studies on CD8+ T-cell responses focused mainly on viral and intracellular parasite infections. Here we investigated CD8+ T-cell responses upon Bordetella pertussis infection in infants, children, and adults and pertussis vaccination in infants. Filamentous hemagglutinin-specific IFN-γ secretion by circulating lymphocytes was blocked by anti-MHC-I or -MHC-II antibodies, suggesting that CD4+ and CD8+ T lymphocytes are involved in IFN-γ production. Flow cytometry analyses confirmed that both cell types synthesized antigen-specific IFN-γ, although CD4+ lymphocytes were the major source of this cytokine. IFN-γ synthesis by CD8+ cells was CD4+ T cell dependent, as evidenced by selective depletion experiments. Furthermore, IFN-γ synthesis by CD4+ cells was sometimes inhibited by CD8+ lymphocytes, suggesting the presence of CD8+ regulatory T cells. The role of this dual IFN-γ secretion by CD4+ and CD8+ T lymphocytes in pertussis remains to be investigated.